Caracterização morfológica dos espermatozoides de jabuti-piranga Chelonoidis carbonaria Spix, 1824 - Araújo, Igor Carrijo Fernandes de (2022)
Chelonians are reptiles that has a good capacity to live for long years in captivity, this specie belongs to genus Chelonidis and occur throughout South America. Jabuti-piranga (Chelonoidis carbonaria Spix, 1824) is considered the most bred chelonian in captivity, but little is known about its reproduction and research is scarce about the characteristics of its sperm cells. The aim of this study was to evaluate sperm morphology and its alterations in jabuti-piranga. Semen samples from nine animals previously collected in other studies and which were located at the Animal Reproduction Laboratory of the Federal University of Uberlândia were used. The sperm conformation was analyzed by photomicrographs that were obtained in a Leica DM500 microscope and the analysis of the captured images was performed in the “open source” software Image J, to obtain information regarding the dimensions of total length, head, middle piece and tail of sperm. Sperm morphology was evaluated by wet-mount preparation (one drop of semen in a glass slide covered by a coverslip) by phase-contrast microscopy, verifying the defects presented by the spermatozoa. Semen was also stained with Red Congo in a glass slide. Data were presented descriptively. The average dimensions in length found for the spermatozoa were: head 15.91 ± 0.89 µm; middle piece, 4.64 ± 0.32 µm; and tail 47.56 ± 1.61 µm; and the total length found was 68.12 ± 1.74 µm. The most frequent abnormalities found were midpiece defects, abnormal head shapes, bent tail, normal isolated head and folded tail. More studies are still needed on these reptiles in order to define their reproductive parameters.